P661Melanoma tumor in mice alters cardiac metabolism and signaling and promotes heart failure in part by STAT3 activation. (15th July 2014) - Stapel, B; Thackeray, J; Haghikia, A; Ricke-Hoch, M; Erschow, S; Bengel, F; Hilfiker-Kleiner, D
Abstract: Purpose: Patients suffering from heart failure or advanced cancer share clinical symptoms including limited exercise capacity, shortness of breath and early fatigue, and develop skeletal and cardiac muscle atrophy. The systemic effects of cancer on the heart are poorly understood. We investigated molecular and metabolic changes of the heart in a B16F10 melanoma mouse cancer model. Methods: B16F10 melanoma tumor was induced by intraperitoneal implantation of B16F10 cells. Morphological, histological and molecular biological (Western Blot, qRT-PCR) analyses, echocardiography and glucose uptake by FDG-PET were carried out 3 weeks later. Results: Tumor growth was confirmed morphologically and by FDG-PET analysis. Tumor-bearing wildtype (C57BL6) mice displayed cardiac atrophy and high mortality (control: 0% vs tumor mice: 66%, P<0.01, n=17-25). In surviving tumor mice, systolic function was depressed (control, FS: 39% vs tumor mice, FS: 23%, P<0.01, n=9-12) and LV wall thickness was reduced. Total MHC protein was decreased (-30%) while tropomyosin and troponin T level were not altered and no changes in LV tissue composition, e.g. fibrosis or inflammation were detected in tumor mice compared to controls. Reduced cardiac FDG uptake in tumor mice suggests impaired myocardial glucose metabolism (-81% vs baseline prior tumor, P<0.01, n=5) paralleled by increased FDG uptake in the growing tumor. mRNA level of CPT1a and b, two key enzymes of fatty acid oxidation, were increased (CPT1a: +2.2-fold; CPT1b: +1.7-fold; P<0.01) and protein level of fatty acid transporter CD36 were significantly elevated (+1.8-fold; P<0.05) in tumor mice, indicating compensatory upregulation of fatty acid utilization. Analysis of myocardial signaling pathways revealed strong induction of STAT3 phosphorylation (tumor mice: 85-fold, P<0.01, n=5) while activation of p38, AKT, and ERK1/2 were unaltered. Conditioned medium from B16-F10 cells induced constitutive activation of STAT3 signaling by 5-fold (P<0.01) over 3 days, and was associated with downregulated protein expression of glucose transporter 4 (-27%, P<0.05). Mice with a cardiomyocyte-specific knockout of STAT3 (αMHC-Cre; STAT3flox/flox: CKO, n=4) were protected from B16F10-induced heart failure compared to wildtype siblings (STAT3flox/flox, n=6: WT, FS: 27% vs CKO, FS: 58% P<0.05). Conclusion: B16F10 melanoma tumor evokes alterations in cardiac signaling, induces changes in myocardial metabolism and promotes cardiac atrophy and failure. At least part of these adverse effects of B16F10 melanoma on the heart seem to be mediated by constitutive activation of STAT3 in cardiomyocytes.